PENGARUH TINGKAT PENDIDIKAN, PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI PADA PT.BANK PEMBANGUNAN DAERAH BALI CABANG UTAMA DENPASAR - Ida Ayu Juwita Apsari; I Nyoman Mustika; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Development in the industrial sector is one of the development priorities which is expected to be able to bring about fundamental changes in other economic structures, so that progress achieved in the industrial sector will be followed by progress in other sectors. This study aims to determine the effect of education level, career development and organizational commitment on employee performance at PT.Bank Pembangunan Daerah Bali Denpasar Main Branch. Companies engaged in the service sector. The object of research in this study is the level of education, career development and organizational commitment to employee performance at PT. Bali Regional Development Bank Denpasar Main Branch. The total population used in this study was 163 employees with a sample obtained from the calculation of the Slovin formula of 62 employees. The technique used is stratified random sampling. Data collection was carried out through observation, interviews and questionnaires. The data analysis technique used was multiple linear regression analysis which was processed using the SPSS version 25 For Windows program. The results of this study indicate that the level of education has a positive and significant effect on PT. Bank Pembangunan Daerah Bali, Denpasar main branch. Career development has a positive and significant effect on employee performance at PT. The Bali Regional Development Bank Denpasar main branch has a positive and significant effect. Organizational Commitment has a positive and significant effect on employee performance at PT. The Bali Regional Development Bank Denpasar main branch has a positive and significant effect.